2017
DOI: 10.1016/j.jsxm.2017.10.064
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Motivations Before and Psychosexual Outcomes After Genital Gender-Confirming Surgery in Transmen

Abstract: Background Genital dissatisfaction is an important reason for transmen to undergo genital gender-confirming surgery (GCS; phalloplasty or metoidioplasty). However, little is known about motives for choosing specific techniques, how transmen benefit postoperatively, and whether psychosexual outcomes improve. Aim To evaluate motivations for and psychosexual outcomes after GCS. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 21 publications
2
51
2
1
Order By: Relevance
“…Looking at the limited data, postsurgical patients have retrospectively reported motivations of gender confirmation, appearance (including size), and standing to urinate, as well as sexual function goals, and some of those patients have expressed regret at the type of surgery that was chosen—although not at having genital surgery. 13 These are also the areas in which postoperative satisfaction has been addressed. 3,13,14 As such, these areas were used as the basis for the development of the initial scale, a 7-item quantitative scale with four additional open-ended questions to generate discussion about expected patient concerns, which could be used as a decision-making tool to determine both the appropriateness of a particular type of surgery and the degree to which patient expectations are realistic or not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking at the limited data, postsurgical patients have retrospectively reported motivations of gender confirmation, appearance (including size), and standing to urinate, as well as sexual function goals, and some of those patients have expressed regret at the type of surgery that was chosen—although not at having genital surgery. 13 These are also the areas in which postoperative satisfaction has been addressed. 3,13,14 As such, these areas were used as the basis for the development of the initial scale, a 7-item quantitative scale with four additional open-ended questions to generate discussion about expected patient concerns, which could be used as a decision-making tool to determine both the appropriateness of a particular type of surgery and the degree to which patient expectations are realistic or not.…”
Section: Resultsmentioning
confidence: 99%
“…13 These are also the areas in which postoperative satisfaction has been addressed. 3,13,14 As such, these areas were used as the basis for the development of the initial scale, a 7-item quantitative scale with four additional open-ended questions to generate discussion about expected patient concerns, which could be used as a decision-making tool to determine both the appropriateness of a particular type of surgery and the degree to which patient expectations are realistic or not. In response to reviewer feedback, that scale was later revised to include an additional question about the importance of phallus appearance (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…89,90 In trans AFAB people with phalloplasty, sexual activity was higher (masturbation and with partner), and they used their genitals more frequently during sex compared with before surgery (31%e78%). 91 Sexual expectations were more frequently met in the group with an erection prosthesis (compared with those without), but pain during intercourse was more often reported. 45 However, in most of the studies that were selected in the review period, the overall data were limited, heterogeneous, of very low quality, and validated measurement tools were missing.…”
Section: Evidencementioning
confidence: 96%
“…10,18 At the same time, despite extensive preoperative counseling, postoperative satisfaction varies, which has partially been attributed to a mismatch between expectations and surgical outcomes in certain individuals. 14,15,19,20 Numerous studies showed that decision aids (DAs) improve the patients' ability to make an informed choice by enhancing the patients' knowledge and participation in the process, help create more realistic expectations of potential benefits and harms of treatment, and support patients to make a decision as per their informed values. 1,21e24 No such data have been described for surgical decision-making accustomed to the transgender population.…”
Section: Introductionmentioning
confidence: 99%